Anger’s moderating influence on the relationship between victimization and perpetration of domestic violence and abuse in patients suffering from severe mental illness. Insights from a cross sectional study using moderated mediation analysis - Ruijne, Roos Eva; Zarchev, Milan; Henrichs, Jens; Garofalo, Carlo; Bogaerts, Stefan; Mulder, Cornelis Lambert; Kamperman, Astrid (Frontiers in Psychiatry, 2024)
IntroductionDomestic violence and abuse (DVA) are prevalent among persons with severe mental illness (SMI), being involved as victim, perpetrator, or both.AimsTo assess rates of DVA victimization and perpetration in patients with SMI. We also aimed to assess whether DVA victimization was associated with DVA perpetration, and whether this was mediated by dispositional anger in patients with SMI. Lastly, we aimed to examine whether gender moderated the associations between DVA victimization and perpetration.MethodsWe conducted a nation-wide survey on victimization in patients with SMI. In 942 patients DVA perpetration of physical assault and victimization of physical assault, sexual coercion or psychological aggression over the past year were assessed using the revised Conflict Tactics Scale. Anger was assessed using the dispositional anger reactions scale. Correlation and mediation analyses were conducted, followed by a moderated mediation to assess whether effects of anger differed between men and women.ResultsThe prevalence rate of perpetration of physical assault was 22%, for victimization 27% and 52% for both. We found a strong positive correlation between perpetrated physical assault and victimization of mild physical assault and between both the perpetration and victimization of severe physical assault. Anger mediated the link between being a victim of psychological aggression and being a perpetrator of DVA. Women were more likely to perpetrate violence if they were victims of mild physical assault compared to men. Other moderation effects by gender were not observed.Conclusion and implicationsThis study reveals persistent high DVA rates among patients with SMI. Overall, anger had no mediating effect on the association between victimization and perpetration of violence, except for psychological aggression and perpetration of DVA. This study emphasizes the importance of routine violence discussions in SMI care while taking context into account. However, further research on underlying mechanisms and interventions to improve discussions and care for victims and/or perpetrators of DVA is necessary.